Activation of aryl halides by nickel(I) pincer complexes: reaction pathways of stoichiometric and catalytic dehalogenations - Rettenmeier, Christoph Alexander; Wenz, Jan; Wadepohl, Hubert; Gade, Lutz H. (Inorganic chemistry, 2016)
Homolytic C-X bond cleavage of organohalides by the T-shaped nickel(I) complexes [LigNiI] 1 bearing the iso-PyrrMeBox ligand had been found previously to be the crucial activation step in the asymmetric hydrodehalogenation of geminal dihalides. Here, this mechanistic investigation is extended to aryl halides, which allowed a systematic study of the activation process by a combination of experimental data and density functional theory modeling. While the activation of both aryl chlorides and geminal dichlorides appears to proceed via an analogous transition state, the generation of a highly stabile nickel(II)aryl species in the reaction of the aryl chlorides for the former represents a major difference in the reactive behavior. This difference was found to have a crucial impact on the activity of these nickel pincer systems as catalysts in the dehalogenation of aryl chlorides compared to geminal dichlorides and highlights the importance of the regulatory pathways controlling the nickel(I) concentration throughout the catalysis. These results along with the identification and characterization of novel nickel(II)aryl species are presented.
Gesehen am 22.10.2021